An empirical analysis of prepackaged bankruptcies - Tashjian, Elizabeth; Lease, Ronald C.; McConnell, John J. (Journal of Financial Economics, 1996)
We provide comprehensive data on the attributes and outcomes of the restructuring process for a sample of 49 financially distressed firms that restructured by means a prepackaged bankruptcy. Our findings complement previous research on out-of-court restructurings and traditional Chapter 11 filings. By most measures, including the time spent in reorganization, the direct fees as a percent of pre-distress assets, the recovery rates by creditors, and the incidence of violation of absolute priority of claimholders, we find that prepacks lie between out-of-court restructurings and traditional Chapter 11 bankruptcies.